2014
DOI: 10.1080/15374416.2014.910787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity in Adolescents’ Depressive Symptoms in Response to Victimization

Abstract: Objective This study had two objectives: first, to determine the degree to which experiences of victimization by peers during adolescence led to a subsequent rise in depressive symptoms; second, to identify genetic markers that predict depressive reactivity to victimization. Method We used a cohort sequential design to obtain a longitudinal sample of 1,475 adolescents (3,263 observations) in grades 8 to 12 (56% female; 47% Black, 46% White). Multilevel growth curve models were used to assess whether victimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Notably, though, a study of Chinese adolescents found that it was Val-BDNF carriers who proved most susceptible to depressive symptoms in the face of stressful life events (Chen et al 2012). Such results would seem to be in line with work with Mexican adolescents (12-17 years) showing BDNF Val/Val homozygotes to be most at risk of depression when facing cumulative psychosocial adversities (Cruz-Fuentes et al 2014), and with U.S. adolescents indicating that Val-BDNF carriers manifested the most depressive symptoms when victimized by their peers (Gottfredson et al 2014). Collectively, the work just cited points to potential developmental, cultural, and ethnic variation in how the BDNF Val66Met polymorphism interacts with the environment in predicting depression.…”
Section: Bdnf Val66met 3 Environment On Depressionsupporting
confidence: 76%
See 1 more Smart Citation
“…Notably, though, a study of Chinese adolescents found that it was Val-BDNF carriers who proved most susceptible to depressive symptoms in the face of stressful life events (Chen et al 2012). Such results would seem to be in line with work with Mexican adolescents (12-17 years) showing BDNF Val/Val homozygotes to be most at risk of depression when facing cumulative psychosocial adversities (Cruz-Fuentes et al 2014), and with U.S. adolescents indicating that Val-BDNF carriers manifested the most depressive symptoms when victimized by their peers (Gottfredson et al 2014). Collectively, the work just cited points to potential developmental, cultural, and ethnic variation in how the BDNF Val66Met polymorphism interacts with the environment in predicting depression.…”
Section: Bdnf Val66met 3 Environment On Depressionsupporting
confidence: 76%
“…We focused on adolescence because most previous G 9 E studies focused on depression were of adults, with earlier reviewed research suggesting that the interaction between BDNF gene and environment may vary across development (e.g., Casey et al 2009;Lenroot and Giedd 2011). Our findings, together with prior adolescent studies (Chen et al 2012;Cruz-Fuentes et al 2014;Gottfredson et al 2014), support the propostion that BDNF Val66Met 9 Environment might vary between adolescents and adults. Specifically, the Val version of BDNF appears to confer heightened susceptibility to environmental influences in the case of youth, whereas the Met version of BDNF operates in this manner with regard to depression and adversity in the case of adults (see meta-analysis in Hosang et al 2014).…”
Section: Discussionsupporting
confidence: 65%
“…To gain insight into the neural mechanisms associated with the negative impact of adolescent bullying and the expression of depression-related symptomatology, we used the social defeat stress model of depression (Gottfredson et al., 2015, Kudryavtseva et al., 1991). We selected this preclinical behavioral approach because it can mimic some of the negative emotional and physical aspects of bullying (Bjorkqvist, 2001), resulting in depression-related behavior (Krishnan et al., 2007, Yu et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis shows that the BDNF Val66Met polymorphism serves as a moderator of the life stress-depression association; individuals with the Met allele, in the presence of environmental risk, have higher rates of depression (Hosang, Shiles, Tansey, McGuffin, & Uher, 2014). Similar to adult research, the BDNF Val66Met has been found to interact with environmental stressors in the prediction of adolescent depressive symptoms; however, the particular allele (Val versus Met) associated with conferring greater risk varies across different investigations during adolescence (Carver, Johnson, Joormann, LeMoult, & Cuccaro, 2011; Chen, Li, McGue, 2012; 2013; Gottfredson, Foshee, Ennett, Haberstick, & Smolen, 2015). It has been posited that which allele of the BDNF Val66Met polymorphism that is associated with poorer phenotype outcomes may vary as a function of development (Casey et al, 2009).…”
mentioning
confidence: 71%